The machine that changed the world : the story of lean production : how Japan's secret weapon in the global auto wars will revolutionize western industry - Womack, James P.; Jones, Daniel T.; Roos, Daniel (New York: HarperPerennial, 1991)
"James P. Womack, Daniel T. Jones and Daniel Roos Bibliotheek François Vercammen"